Rancang Bangun Sistem Inventory Gudang Menggunakan Metode Waterfall Studi Kasus Di Cv. Aqualux Duspha Abadi Kudus Jawa Tengah - Edy Listiyan; Egia Rosi Subhiyakto (KONSTELASI: Konvergensi Teknologi dan Sistem Informasi, 2021)
Information technology is increasingly advanced and continues to develop rapidly with the times. Information technology covers almost all areas of life, including industry. CV. Aqualux Duspha Abadi is a water treatment & water purifier company based in Kudus, Central Java. This research was conducted to build an Inventory System application that aims to overcome several existing problems. The problems that occurred with the previous inventory system were monitoring the entry and exit of goods as well as the discrepancy between the number of goods and the data. This research uses the waterfall development method, this method has very sequential steps so that the development of a system will be more structured. In this study, researchers tested the functionality of the system using black-box testing, and to test the level of satisfaction of users, researchers used the user acceptance test (UAT). The result of this research is an android based inventory system application. Data from black-box testing is 100% valid and UAT test data shows a satisfaction rate above 90%.Keywords: Inventory System, Android, Waterfall, Black Box Testing, User Acceptance Test (UAT)